Moodiness in ADHD A Clinician's Guide (Springer International Publishing, 2018)
This book gives clinicians a framework and tools to accurately assess moodiness in patients with ADHD, and to provide the most appropriate pharmacological and psychosocial treatments for such problems. This book reviews the assessment and treatment of moodiness in ADHD patients of all ages, but focuses primarily on children and adolescents. Chapters review effective assessment strategies for various potential causes of moodiness in patients with ADHD, then psychosocial and pharmacological treatments and their empirical basis. Specific chapters are devoted to the moodiness characteristic of ADHD itself, and to other disorders co-occurring with it such as disorders of mood, anxiety, trauma-exposure, disruptive behaviors, autism, substance use, and medical problems. The also text includes useful case summaries and tables to illustrate key clinical points useful in working with these patients. Moodiness in ADHD is a potentially vital resource for clinicians wanting to improve their skill working with patients having these challenging problems.